2018
DOI: 10.1093/molehr/gay001
|View full text |Cite
|
Sign up to set email alerts
|

Epididymal cysteine-rich secretory proteins are required for epididymal sperm maturation and optimal sperm function

Abstract: This study was funded by the National Health and Medical Research Council, the Victorian Cancer Agency and a scholarship from the Chinese Scholarship Council. The authors have no conflicts of interest to declare.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
43
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(48 citation statements)
references
References 46 publications
4
43
0
1
Order By: Relevance
“…Differences in the genetic context and environmental conditions might also explain recent observations published during the preparation of this manuscript showing the absence of fertility and in vitro fertilization defects in DKO mice lacking CRISP1 and CRISP4 and exhibiting sperm functional defects (i.e. motility, AR, pTyr) and immune infiltrates in the epididymal stroma of old males 70 .…”
Section: Discussionmentioning
confidence: 84%
“…Differences in the genetic context and environmental conditions might also explain recent observations published during the preparation of this manuscript showing the absence of fertility and in vitro fertilization defects in DKO mice lacking CRISP1 and CRISP4 and exhibiting sperm functional defects (i.e. motility, AR, pTyr) and immune infiltrates in the epididymal stroma of old males 70 .…”
Section: Discussionmentioning
confidence: 84%
“…Starting from the 1960s important sperm functions, such as the acquisition of sperm progressive motility and fertilizing capacity, were hypothesized under the control of the epididymis [ 56 , 57 ]. Considering that it is not surprising that epididymosomes convey to SPZ a large cargo of proteins encompassing key classes of enzymes, chaperones and structural proteins; for example, the cysteine-rich secretory protein 1 (CRISP1) regulates Ca 2+ channels in the sperm membrane [ 58 ], the sperm adhesion molecule 1 (SPAM1, also known as PH-20) is involved in sperm-zona pellucida adhesion [ 59 ] and the macrophage migration inhibitory factor (MIF) actively participates in sperm motility acquisition [ 60 ]. Epididymosomes also contain proteins providing antimicrobial and proteolytic attack protection [ 12 ], and glutathione peroxidase (GPX) enzymes preventing premature acrosome reaction and protecting sperm from oxidative stress [ 61 , 62 ].…”
Section: Exosomes In the Male Reproductive Tract: Their Potential mentioning
confidence: 99%
“…The potential role of CRISP4 in fertilization and fertility was investigated by different groups using KO models (Gibbs et al ., ; Turunen et al ., ; Carvajal et al ., ; Hu et al ., ). Whereas males lacking CRISP4 were fertile in different genetic backgrounds (Gibbs et al ., ; Turunen et al ., ; Carvajal et al ., ; Hu et al ., ), several sperm capacitation‐associated parameters as well as the sperm fertilizing ability were differently affected in each strain (Turunen et al ., ; Carvajal et al ., ; Hu et al ., ). Spermatozoa from CRISP4 KO mice generated by our group failed to undergo protein tyrosine phosphorylation and the progesterone‐induced acrosome reaction during capacitation and were unable to fertilize cumulus‐invested, ZP‐intact and ZP‐free eggs (Carvajal et al ., ).…”
Section: Cysteine Rich Secretory Proteinmentioning
confidence: 97%
“…Results showed that CRISP1 mutant spermatozoa exhibited defects in capacitation‐associated parameters as well as in their ability to bind to the ZP and to fuse with the egg, confirming the roles of CRISP1 in sperm‐ZP binding and gamete fusion previously described (Rochwerger et al ., ; Cohen et al ., ; Busso et al ., ). However, in spite of the important roles of CRISP1 in fertilization, CRISP1 KO males were as fertile as controls (Da Ros et al ., ) even in mice from different genetic backgrounds (Hu et al ., ; Weigel Muñoz et al ., ). Considering the high sequence homology among CRISP family members, these observations support the existence of compensatory mechanisms between homologous CRISP.…”
Section: Cysteine Rich Secretory Proteinmentioning
confidence: 99%
See 1 more Smart Citation